Effect of Population Density on Timing of Oviposition and Brood Size Reduction in the Burying Beetle Nicrophorus pustulatus Herschel (Coleoptera: Silphidae) - Claudia M. Rauter; Renae L. Rust (Psyche: A Journal of Entomology)
Burying beetles (Nicrophorus spp.) bury small carcasses to feed their larvae. Carcasses are a limited, high-quality resource and contests over carcasses become more frequent with increasing population density. Successful beetles kill eggs and larvae present on carcass. In response, females should accelerate oviposition, while offspring development should increase to minimize mortality. Both value of a carcass and frequency of contests decrease as larvae develop. If overproduction of offspring is an insurance against high mortality, females should reduce brood size as carcass value declines. Testing our predictions, we reared female burying beetles, Nicrophorus pustulatus, at high and low densities and compared oviposition and brood reduction. High-density females delayed oviposition, suggesting that high population density imposes nutritional and/or physiological stress. Females responded to the physiological constraints and the potentially high mortality rates of eggs and newly hatched larvae by lengthening oviposition period and changing brood reduction rate.